Chemical Petrology of the Port Coldwell Alkali Intrusive, Marathon, Ontario - Herdman, David J. (My University, 1974)
This study was planned as a combination of detailed field mapping, thin section petrography, whole rock geochemistry and amphibole chemistry of the rocks of the Port Coldwell intrusion. It was hoped that the results of the detailed field mapping would give a clearer picture of the stratigraphy and structure of the intrusion. It was hoped to define the mineralogy and textures of the various phases of the Port Coldwell intrusion enabling a postulation of possible physical conditions under which crystallization occurred. Through whole rock chemical analysis it was hoped to correlate the petrochemistry with the stratigraphy, and so to provide a chemical explanation of the differentiation process. Furthermore, it was hoped to classify the gabbros and through differentiation trends provided by the plots of the analyses, to determine whether the gabbro could be a feasible parent of the other phases of the intrusionThe amphibole found in each phase of the intrusion was to be determined in order to discover elemental trends and to provide corroborating evidence of a differentiation sequence suggested by other sources.
Keywords: chemical petrology; alkali; field mapping; rock geochemistry; amphibole chemistry; petrochemistry